Experiences and considerations about profiles of competitions - Haddad Barthelemy, Jorge (2007)
This study was carried out in the Banco Popular de Ahorro, in Santiago de Cuba. Duringthree years, different Profiles of Directive Competitions were made as well as a Unique or Generic Profile, adaptable to any executive of this or other organizations. Different con- ceptions of competitions were obtained and confirmed, such as simple, compound, basic, secondary, generic and specific competitions. Various experiences were confirmed, such as the importance of establishing their dimensions, contradictions and similarities between competitions and values, their possibility to focus on different organizational tasks, such as the improvement of the environment, the quality in the performance of top and intermediate management, technicians and workers, with the objective of improving the performance of the employees and the organization.